The use of films and tv series in teaching and learning process of Economy (Dissertare, 2016)
This paper presents the preliminary results of a research which focuses on the use of films and TV series as didactic strategy for teaching and learning of economic area subjects for computer science engineering at UCLA. The objectives of this study include both the design of the mentioned strategy and the evaluation of the results derived from its application during the academic periods between May 2016 and December 2017, including the perspective of students and teachers in the evaluative aspect. The advance in this article only covers the design phase. The approach of this study is predominantly quantitative, with some features of qualitative paradigm, aspects that are combined in framework of a documentary and field design using the techniques of bibliographic review, survey and observation. Based on the application of the first mentioned technique, it was possible to verify the existence of considerable interest in the use of the films and TV series, as a didactic strategy for the teaching-learning of Economy, with positive results, mainly with the interest of the students in the economic contents. From literature review, useful contributions have been found as reference to the design of the didactic proposal of this work. As a final aspect, it is proposed to extend the use of the strategy analyzed to other engineering careers and to form academic networks dedicated to the study of this subject.
Keywords: Economy; films; series; didactic strategy